Case report about the bioclimatology and ambience of the swine productive unit in a federal educational institution (Research, Society and Development, 2023)
Brazil is currently one of the main pork producing and exporting countries in the world. For the maintenance of this position, it is necessary to invest in technology that seeks the animal's welfare through bioclimatology and ambience. The biggest challenge faced in swine production is thermal comfort, as these animals are highly affected by high and low temperatures. Therefore, the objective of this work was to evaluate if the swine breeding farm of the federal educational institution meets the basic requirements of bioclimatology and ambience. For this, data of temperature, humidity, precipitation and wind speed, between the months of January and September, were collected. Besides this, measurements of the sheds, sizing of the stalls, type of floor used, type of roof, presence of skylight, ceiling and curtain and number of animals, doing comparisons with the literature and checking if the requirements were met. Some requirements are well established, such as the number of animals per shed and the use of curtains in the maternity and growing sector. Some modifications could be applied at the farm, such as the application of a ceiling in conjunction with a fan and use of artificial ventilation associated with nebulization. These adaptations would be important to better meet the need for thermal comfort, which would have a positive impact on the welfare of housed animals. It is noteworthy that the sector must also adapt to the new welfare regulations published in 2020.